Balance improvements and golf swing kinematic consistency with eight week balance intervention - Owen, M. K.; Gambill, J. A.; Van Damme, K. N.; Byrd, J. E.; DesJardins, J. D. (Journal of Sports Research, 2020)
The purpose of the study was to isolate the relationship between balance and swing kinematics for collegiate level male golfers. Eight National Collegiate Athletic Association (NCAA) Division I golfers completed an eight-week training program targeting improving balance. All golfers were assessed for postural stability and swing kinematics before and after the balance training program. Golfers completed 10 swings with a driver, and swing kinematics were measured using 3D motion capture (Qualisys AB). Postural stability results showed decreases in center-of-pressure (COP) deviation for single leg, eyes closed stance conditions were significant (p<0.05). Changes in Balance Error Scores (BES) were not significant (p>0.05) for any stance condition following training intervention. Range values (maximum-minimum) for club head speed (CHS), club path, and face angle stayed the same or decreased following the training intervention but were not significant (p>0.05). Key positions in the golf swing, including pelvis and torso angles at the top of the swing and impact were unaffected by the balance training (p>0.05). Pearson`s values indicated a low degree of correlation between postural stability and swing kinematic consistency, as measured by variance. While postural stability improved following golf specific balance training, individual swing kinematics and swing kinematics consistency were unaffected. This study is one of very few studies which have investigated consistency in golf swing kinematics as well as the effect of strength and conditioning training, specifically balance training, on the consistency of golf swing kinematics.